2003
DOI: 10.1080/0963828021000030927
|View full text |Cite
|
Sign up to set email alerts
|

Posteroanterior motion test of a lumbar vertebra: accuracy of perception

Abstract: An electromechanical spinal model can be used as training tool along with an oscilloscope. Longer training may be needed for the force than the displacement for accurate perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…There seems to be a general tendency towards higher intraobserver reliability compared to interobserver results. [24][25][26][27][28][29][30][31][32] The present results point somewhat in the same direction. In a recent systematic review of the literature on this topic, higher reproducibility of regional compared to segmental manual mobilizations has been reported.…”
Section: Discussion Reproducibilitysupporting
confidence: 75%
“…There seems to be a general tendency towards higher intraobserver reliability compared to interobserver results. [24][25][26][27][28][29][30][31][32] The present results point somewhat in the same direction. In a recent systematic review of the literature on this topic, higher reproducibility of regional compared to segmental manual mobilizations has been reported.…”
Section: Discussion Reproducibilitysupporting
confidence: 75%
“…There seems to be a general tendency towards higher intra-observer reliability compared to inter-observer results (Panzer, 1992;Harrison et al, 1998;Hawk et al, 1999;Vincent-Smith and Gibbons, 1999;Christensen et al, 2002a,b;Billis et al, 2003;Bjornsdottirt and Kumar, 2003;Kachingwe and Phillips, 2005;Johansson, 2006). In a recent review on this topic additionally higher reproducibility of regional compared to segmental manual mobilizations have been reported (Seffinger et al, 2004).…”
Section: T-valuementioning
confidence: 87%
“…Simmonds et al (1995) and Bjornsdottir and Kumar (2003) reported a large variation in perception of applied force and displacement produced by experienced manual therapists on a single segment electromechanical spinal model (Kumar, 1995).…”
Section: Male Stiffness and Compliancementioning
confidence: 98%